2018
DOI: 10.3389/fnmol.2018.00073
|View full text |Cite
|
Sign up to set email alerts
|

Blood Gene Expression Profile Predicts Response to Antipsychotics

Abstract: Antipsychotic drugs are one of the largest types of prescribed drugs and have large inter-individual differences in efficacy, but there is no methodology to predict their clinical effect. Here we show a four-gene blood expression profile to predict the response to antipsychotics in schizophrenia patients before treatment. We sequenced total mRNA from blood samples of antipsychotic naïve patients who, after 3 months of treatment, were in the top 40% with the best response (15 patients) and in the bottom 40% wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…In the clinical settings, because antipsychotics have large interindividual differences in efficacy, there is no methodology to predict the effect of antipsychotics 77 . Although much progress has been made on antipsychotic drug development, precise mechanisms behind the action of antipsychotics are poorly understood 78,79 . Non-genetic factors such as epigenetic modifications are known to be involved in the effect of antipsychotics 80 .…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical settings, because antipsychotics have large interindividual differences in efficacy, there is no methodology to predict the effect of antipsychotics 77 . Although much progress has been made on antipsychotic drug development, precise mechanisms behind the action of antipsychotics are poorly understood 78,79 . Non-genetic factors such as epigenetic modifications are known to be involved in the effect of antipsychotics 80 .…”
Section: Discussionmentioning
confidence: 99%
“…29,33,[64][65][66] The slow onset of response to lurasidone and other atypicals in most TRS patients suggests that immediate receptor-mediated actions affects gene expression leading to metaplastic changes in synaptic structure and function that are the ultimate basis for improvement in psychopathology, cognition, and ultimately work and social function in TRS patients. 30,[79][80][81][82] We have recently demonstrated that genes associated with prediction of the response of acutely psychotic patients to lurasidone are related to synaptic proteins in both excitatory and inhibitory synapses. 57,58 Thus, it is important to determine if TRS patients who do not respond to one AAPD might respond to another.…”
Section: Mechanism Of Action Of Lurasidone and Other Aapds In Trsmentioning
confidence: 99%
“…Thus, astrocyte dysfunction in schizophrenia is anticipated to have wide-ranging effects on the development and maintenance of salient neural circuitry. An association between HMOX1 induction and schizophrenia has emerged from a growing number of human and animal studies (Duan and others 2018; Prabakaran and others 2004; Rajdev and others 1998; Rukova and others 2015; Sainz and others 2018; Schiavone and others 2017; Takao and others 2013; Zhao and others 2018). GFAP.HMOX1 0-12m mice recapitulate astrocyte-driven disease, oxidative stress and mitochondrial insufficiency documented in the brains of schizophrenic subjects (see Schipper and others 2019).…”
Section: Abnormal Morphology Of the Dentate Gyrus In An Animal Modelmentioning
confidence: 99%